2018
DOI: 10.3389/fnhum.2018.00214
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis of the Emotional Conflict Processing in Major Depression: ERPs and Source Localization Analysis on the N450 and P300 Components

Abstract: Objects: Effective psychological function requires that cognition is not affected by task-irrelevant emotional stimuli in emotional conflict. Depression is mainly characterized as an emotional disorder. The object of this study is to reveal the behavioral and electrophysiological signature of emotional conflict processing in major depressive disorder (MDD) using event-related potentials (ERPs) and standardized low-resolution brain electromagnetic tomography (sLORETA) analysis.Method: We used a face–word Stroop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 66 publications
3
8
0
Order By: Relevance
“…The midfrontal location of the congruency effect in this study comports with extensive adult literature showing frontal midline ERPs and activation in the anterior cingulate cortex (ACC) and prefrontal cortex (PFC) in response to stimulus congruency in a variety of emotional and non-emotional contexts (Kerns, 2006; Töllner et al, 2017; West, Bailey, Tiernan, Boonsuk, & Gilbert, 2012; Zhu et al, 2018). Although results have been mixed, some research has shown thickness differences in the ACC of children who have experienced maltreatment (Kelly et al, 2013) and researchers have also found differences in prefrontal areas in children who have experienced institutionalization (McLaughlin et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…The midfrontal location of the congruency effect in this study comports with extensive adult literature showing frontal midline ERPs and activation in the anterior cingulate cortex (ACC) and prefrontal cortex (PFC) in response to stimulus congruency in a variety of emotional and non-emotional contexts (Kerns, 2006; Töllner et al, 2017; West, Bailey, Tiernan, Boonsuk, & Gilbert, 2012; Zhu et al, 2018). Although results have been mixed, some research has shown thickness differences in the ACC of children who have experienced maltreatment (Kelly et al, 2013) and researchers have also found differences in prefrontal areas in children who have experienced institutionalization (McLaughlin et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…These results suggest that perceptual processes involved in the early stages of face processing are impaired in MDD. Zhu et al [84] assessed the amplitudes and latencies of N450 and P300 components in MDD and control groups, using a face-word Stroop task. Participants were presented with sad and happy face stimuli with the words happy or sad superimposed on them in incongruent and congruent ways and had to indicate the emotion expressed by the face, ignoring the word.…”
Section: ) Erp Componentsmentioning
confidence: 99%
“…When confronted with cognitive conflicts, individual dependent on a system of cognitive control to help them resolve the current conflict they are experiencing 37 . Major depression presented abnormal conflict processing in cognitive conflict tasks 38 , which can arise from this emotional interference and can compromise the ability to complete tasks requiring cognitive control 39 . Particularly, cognitive control resources can regulate and control other cognitive processes during moral decision-making that may be crucial for making moral judgments 5 .…”
Section: Discussionmentioning
confidence: 99%